The drug titration paradox: more drug does not correlate with more effect in individual clinical data. (December 2022) - Schnider, Thomas W.; Minto, Charles F.; Luginbühl, Martin; Egan, Talmage D.
Abstract: Background: A fundamental concept in pharmacology is that increasing dose increases drug effect. This is the basis of anaesthetic titration: the dose is increased when increased drug effect is desired and decreased when reduced drug effect is desired. In the setting of titration, the correlation of doses and observed drug effects can be negative, for example increasing dose reduces drug effect. We have termed this the drug titration paradox. We hypothesised that this could be explained, at least in part, by intrasubject variability. If the drug titration paradox is simply an artifact of pooling population data, then a mixed-effects analysis that accounts for interindividual variability in drug sensitivity should 'flip' the observed correlation, such that increasing dose increases drug effect. Methods: We tested whether a mixed-effects analysis could correctly reveal the underlying pharmacology using previously published data obtained during automatic feedback control of mean arterial pressure (MAP) with alfentanil (effect site concentration, CeAlf ) during surgery. The relationship between MAP and CeAlf was explored with linear regression and a linear mixed-effects model. Results: A linear mixed-effects model did not identify the correct underlying pharmacology because of the presence of the titration paradox in the individual data. Conclusions: The relationship between drug dose and drug effect must be determined under carefully controlled experimental conditions. In routine care, where the effect is profoundly influenced by varying clinical conditions and drugs are titrated to achieve the desired effect, it is nearly impossible to draw meaningful conclusions about the relationship between dose and effect.